A Systems Approach to Measuring and Managing Company Performace - Jelínková Lucie; Myšková Renáta (WSEAS Press, 2015)
The key condition in today's tough competitive struggle is the ability to distinguish oneself from the competition. Naturally, an insufficient level of knowledge of modern management theory and deficiencies in systems thinking prevent managers from being able to set a company apart from its competitors. Nevertheless, it is possible to see competitiveness and competitive advantage as one of the decisive factors for a company's performance. A comprehensive information system is decisive for company management and other concerned parties in order to monitor company performance, evaluate and understand it and to reveal all factors affecting its development. Therefore, a systems approach for measuring and managing performance becomes an important condition for successful company management. This report deals with the problematic of the systems approach to measuring and managing performance at a specific manufacturing company. Findings acquired on the basis of an analysis conducted using internal company materials and a managed partially-structured interview are evaluated in the context of theoretical framework to apply the systems approach in the given area. Subsequently, this company's system is described and graphically depicted, and a recommendation is presented for potentially increasing the system's effectiveness.
Systémový přístup k měření a řízení výkonnosti podniku
Keywords: approach; management; performance; system; přístup; řízení; výkonnost; systém